Association of Foot Health and Lower Extremity Function in Older People with Rheumatoid Arthritis: A Cross-Sectional Study - Stolt, Minna; Narsakka, Noora; Katajisto, Jouko; Suhonen, Riitta (KARGER, 2025)
Introduction: Foot health and lower extremity function are important in older people with rheumatoid arthritis (RA), as they maintain and promote these individuals' independent living and functional health. RA is a long-term inflammatory health condition that alters foot structure and function. Relatively little is known about the association between foot health and lower extremity function in older people with RA. Therefore, the aim of the study was to analyse the levels of foot health and lower extremity function in older people with RA and to explore the associations between these factors.
Methods: A cross-sectional survey design study was conducted. The data were collected online in April 2023 from a national association of patients with rheumatic conditions in Finland using two instruments: the Self-administered Foot Health Assessment Instrument (S-FHAI) and the Lower Extremity Function Scale (LEFS). The data were analysed using descriptive and inferential statistics.
Results: Older people with RA (n = 270) reported many foot health problems, the most common of which were foot pain, dry skin, and oedema. Lower extremity function in older people with RA was at the mild-to-moderate functional limitation level and respondents reported major difficulties running or hopping, squatting, carrying out their usual hobbies, performing strenuous activities outside their homes or putting on shoes/socks. Poor levels of foot health were correlated with decreased lower extremity function.
Conclusion: Foot health is associated with lower extremity function in older people with RA. Therefore, it is essential that older people with RA be provided with systematic foot health assessments, care and rehabilitation to promote their lower extremity health and improve their functional health. Multiprofessional collaboration and seamless care chains at different levels of health care could benefit older people with RA looking to maintain their functional ability and - above all - promote their active ageing.